2020
DOI: 10.1002/adma.201907390
|View full text |Cite
|
Sign up to set email alerts
|

Tip‐Induced Inversion of the Chirality of a Molecule's Adsorption Potential Probed by the Switching Directionality

Abstract: The switching behavior of surface‐supported molecular units excited by current, light, or mechanical forces is determined by the shape of the adsorption potential. The ability to tailor the energy landscape in which a molecule resides at a surface gives the possibility of imposing a desired response, which is of paramount importance for the realization of molecular electronic units. Here, by means of scanning tunneling microscopy, a triazatruxene (TAT) molecule on Ag(111) is studied, which shows a switching be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…We have recently shown that N , N ′, N ″-triethyltriazatruxene ( Et TAT , Figure , R = Et) serves as a programmable molecular switch when deposited on Ag(111) . Binding to the substrate results in two degenerate, enantiomeric configurations, R (clockwise rotation for the symmetry equivalent transformations) and S (counterclockwise rotation for symmetry equivalent transformations).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have recently shown that N , N ′, N ″-triethyltriazatruxene ( Et TAT , Figure , R = Et) serves as a programmable molecular switch when deposited on Ag(111) . Binding to the substrate results in two degenerate, enantiomeric configurations, R (clockwise rotation for the symmetry equivalent transformations) and S (counterclockwise rotation for symmetry equivalent transformations).…”
Section: Introductionmentioning
confidence: 99%
“…The reversible and directional switching in either a clockwise ( R surface enantiomer) or counterclockwise ( S enantiomer) direction between these three states was achieved by placing the tip of a scanning tunneling microscope (STM) in a lateral position above a TAT molecule and adjusting the tunneling current and bias voltage. The switching relies on a rocking motion of the Et TAT molecules in a ratchet-like potential yet not on a rotational motion . Hence, the TAT molecules on Ag(111) constitute three-state, trinary-digit (trit) units for on-surface information storage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, no local information on the interactions between water and organic molecules could be obtained. Thus, it is generally intriguing to manipulate each single water molecule in a water-involved structure in situ to detect local intermolecular interactions. …”
Section: Introductionmentioning
confidence: 99%